POLITICAL MOVEMENTS IN IRAQ: THE ROLE OF CIVIL SOCIETY AFTER THE OCTOBER 25 REVOLUTION - Hussein, Kamal (Journal of Learning on History and Social Sciences, 2025)
Objective: This study examines the role of civil society in Iraq’s political movements following the October 25 Revolution (Tishreen Revolution), highlighting its impact on human rights, political accountability, and long-term governance reforms. Method: Employing a mixed-method approach, the study integrates quantitative data from a validated questionnaire and secondary sources, alongside qualitative insights from in-depth interviews with leaders of civil organizations. Results: Findings suggest that the revolution had a positive influence on human rights and civic engagement, though statistical significance was not established. The study underscores civil society's role in fostering political change and citizen participation, despite structural and institutional challenges. Novelty: By providing empirical evidence on the evolving role of civil society in Iraq’s post-revolutionary context, this study contributes to scholarly discourse on political transitions and offers insights for policymakers and international stakeholders aiming to strengthen democratic governance.